2021
DOI: 10.3311/ppci.17298
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Modified Reactive Powder Concrete with Waste Materials Powder Replacement

Abstract: Across the world, a huge amount of waste materials is deposited from different industrial or construction activities. Out of this massive waste quantity, a petite is recycled and remaining is dumped in vulnerable lands. This paper deals with the potential utilization of solid waste in reactive powder concrete, practically powdered glass originating from waste glass bottles and powdered ceramics tile from waste of construction process. First, the optimum ratio of waste pozzolanic material (ceramics to glass rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In this research, we tested the pozzolanic activity [26] of the glass using the SRPS B.C1.018 standard [27]. It classifies the pozzolanic material in three ways: based on the We examined the glass pozzolanic activity based on the mortar's tested mechanical properties according to which the glass must have grains finer than 0.063 mm and it needs to be dried at 98 °C.…”
Section: Materials and Methods 21 Cementitious Materialsmentioning
confidence: 99%
“…In this research, we tested the pozzolanic activity [26] of the glass using the SRPS B.C1.018 standard [27]. It classifies the pozzolanic material in three ways: based on the We examined the glass pozzolanic activity based on the mortar's tested mechanical properties according to which the glass must have grains finer than 0.063 mm and it needs to be dried at 98 °C.…”
Section: Materials and Methods 21 Cementitious Materialsmentioning
confidence: 99%
“…Reducing the amount of waste materials disposed of is the primary objective of trash recycling, which has an adverse effect on the environment. Recycling of waste materials has also been used to provide substitute materials that encourage the slow decline of natural resources, which are being overused [1][2][3][4][5][6] In most places around the country, flexible roadway is the desired kind of pavement for roads and highways. However, creating and maintaining these types of structures requires a significant amount of non-renewable resources and industrial products, including bitumen, aggregates, subbase, cement, lime and other additives.…”
Section: Introductionmentioning
confidence: 99%
“…Copetti et al [22] believe that using silica fume in tire-rubber concretes will increase the compressive strength by about 80% and attribute the improved concrete mechanical properties to reduced volume of the pores (about 13%) and the increased ITZ strength. Strength and water absorption of the modified reactive powder concrete containing powder glass and ceramic were evaluated by Radhi et al [23]. A significant enhancement was observed in mechanical behavior of modified reactive powder concrete containing 15 % waste pozzolanic material [23].…”
Section: Introductionmentioning
confidence: 99%
“…Strength and water absorption of the modified reactive powder concrete containing powder glass and ceramic were evaluated by Radhi et al [23]. A significant enhancement was observed in mechanical behavior of modified reactive powder concrete containing 15 % waste pozzolanic material [23]. Cao et al [24] showed that the workability, compressive strength and durability indicators improved with the increased of glass powder content in concrete.…”
Section: Introductionmentioning
confidence: 99%